ANALYSIS OF THE ESSENCE OF “GOVERNANCE MECHANISM” AND BUILDING UP ITS GENERALIZED DEFINITION - Dukov D.F. (Pressing Problems of Public Administration, 2015)
By taking two different methodological approaches, which are based on the defining of the generic term, essential features and formal notion of the “system”, the article claims to analyze the existing definitions of the notion “governance mechanism” and create two new generalized definitions of that notion.